Antithrombotic Effects of the Novel Small-Molecule Factor XIa Inhibitor Milvexian in a Rabbit Arteriovenous Shunt Model of Venous Thrombosis - Wang, Xinkang; Li, Qiu; Du, Fuyong; Shukla, Neetu; Nawrocki, Andrea R.; Chintala, Madhu (TH Open, 2023)
Background Factor XIa (FXIa) is an emerging therapeutic target, and FXIa inhibition is a promising mechanism to improve therapeutic index over current anticoagulants. Milvexian (BMS-986177/JNJ-70033093) is an oral small-molecule FXIa inhibitor.Objective Milvexian's antithrombotic efficacy was characterized in a rabbit arteriovenous (AV) shunt model of venous thrombosis and compared with the factor Xa inhibitor apixaban and the direct thrombin inhibitor dabigatran.Methods The AV shunt model of thrombosis was conducted in anesthetized rabbits. Vehicle or drugs were administered as intravenous bolus plus a continuous infusion. Thrombus weight was the primary efficacy endpoint. Ex vivo activated partial thromboplastin time (aPTT), prothrombin time (PT), and thrombin time (TT) were measured as the pharmacodynamic responses.Results Milvexian dose dependently reduced thrombus weights by 34.3 ± 7.9, 51.6 ± 6.8 (p < 0.01; n = 5), and 66.9 ± 4.8% (p < 0.001; n = 6) versus vehicle at 0.25 + 0.17, 1.0 + 0.67, and 4.0 ± 2.68 mg/kg bolus + mg/kg/h infusion, respectively. Ex vivo clotting data supported a dose-dependent prolongation of aPTT (with 1.54-, 2.23-, and 3.12-fold increases from baseline upon the AV shunt start), but no changes in PT and TT. Dose-dependent inhibition in thrombus weight and clotting assays was also demonstrated for both apixaban and dabigatran as the references for the model validation.Conclusion Results demonstrate that milvexian is an effective anticoagulant for prevention of venous thrombosis in the rabbit model, which supports the utility of milvexian in venous thrombosis, as seen in the phase 2 clinical study.
Keywords: anticoagulants; factor XI; thrombosis; models; animal; pharmacology